2020
DOI: 10.1029/2020jd032497
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics and Brown Carbon Chromophores of Atmospheric Organic Aerosols Over the Yangtze River Channel: A Cruise Campaign

Abstract: Organic aerosols (OAs) have important influences on the climatic implications and health effects of atmospheric aerosols. Among the complex OA constituents, brown carbon (BrC) accounts for a substantial mass fraction and is of special interest because of its light‐absorbing properties. In this study, the chemical composition of atmospheric OAs over the middle‐lower Yangtze River (MLYR) channel, as well as the BrC, was investigated during a ship cruise campaign in winter 2015. In total, more than 1,000 molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…The BC concentrations in snow were measured by a custom-developed two-sphere integration (TSI) spectrophotometer (Wang et al, 2020b) and have been reported by Shi et al (2020). The distribution of BC concentrations in snow samples is also shown in Fig.…”
Section: Chemical Species Analysismentioning
confidence: 99%
“…The BC concentrations in snow were measured by a custom-developed two-sphere integration (TSI) spectrophotometer (Wang et al, 2020b) and have been reported by Shi et al (2020). The distribution of BC concentrations in snow samples is also shown in Fig.…”
Section: Chemical Species Analysismentioning
confidence: 99%
“…The OH‐initiated oxidation of naphthalene produces a number of different oxygenated compounds with high molecular weight and low‐volatility, which can partition into particles and contribute to SOA mass (Chan et al., 2009; Kautzman et al., 2010; Riva et al., 2015). Naphthoquinone, a naphthalene oxidation product (McWhinney et al., 2013), is commonly found in atmospheric aerosols (e.g., Shanghai, China [Wang et al., 2017]; Tempe, USA [Delhomme et al., 2008]; Kurashiki City, Japan [Oda et al., 2001]; Yangtze River channel [Wang et al., 2020b]), and is known to be an efficient photosensitizer, inducing redox chemistry or producing reactive oxygen species (De Lucas et al., 2014; McNeill & Canonica, 2016). SOA derived from oxidation of naphthalene under high‐NO x conditions has been shown to be weakly fluorescent (Lee et al., 2014), resilient to photobleaching (Aiona et al., 2018), efficient in photosensitizing singlet oxygen in aqueous solutions (Manfrin et al., 2019), capable of photosensitized oxidation of halide ions (Gemayel et al., 2021), and moderately effective in photosensitized oxidation of d‐limonene (Malecha & Nizkorodov, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The system was operated in both ESI+ and ESI− mode with a resolving mass power of 140 000 at m/z 200. A sodium acetate solution (2 mM in 50/50, v/v, ACN/water) was used for the mass calibration; this solution provides a series of negative and positive adduct ions in the scanning range of m/z 50–750 41,42 . The calibration method consisted in filling the syringe with a 2 mM solution of sodium acetate and setting the syringe pump flow rate to 20 µl min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…41,42 This software provides the main functionality for MS data processing: raw data import, mass detection, chromatogram building, deisotoping, alignment, identification, and duplicate peak filtering. The detailed processing steps and settings can be found in Wang et al 42 and in Table S1. Molecular formulas tentatively identified were expressed as C c H h O o N n S s , where c, h, o, n, and s correspond to the numbers of carbon, hydrogen, oxygen, nitrogen, and sulfur atoms in the molecular formula, respectively.…”
Section: Mass Spectrometry Analysismentioning
confidence: 99%